2013
DOI: 10.1073/pnas.1312691110
|View full text |Cite
|
Sign up to set email alerts
|

Cellular organization of cortical barrel columns is whisker-specific

Abstract: The cellular organization of the cortex is of fundamental importance for elucidating the structural principles that underlie its functions. It has been suggested that reconstructing the structure and synaptic wiring of the elementary functional building block of mammalian cortices, the cortical column, might suffice to reverse engineer and simulate the functions of entire cortices. In the vibrissal area of rodent somatosensory cortex, whisker-related "barrel" columns have been referred to as potential cytoarch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 38 publications
4
108
0
Order By: Relevance
“…Anatomical studies have shown that VPM sends multiple projections to the barrels in layer IV and to layer VI of S1 (Bernardo and Woolsey 1987;Killackey 1973;Lorente de No 1922;Woolsey and Van der Loos 1970), whereas POM projections to layer IV terminate mostly in the septa (Chmielowska et al 1989;Fabri and Burton 1991;Koralek et al 1988;Lu and Lin 1993). As the area occupied by barrels in layer IV is considerably larger than the area occupied by septa (Meyer et al 2013;Wimmer et al 2010;Woolsey and Van der Loos 1970), the observation that layer IV matches VPM neural state maps is in line with this anatomical data. However, the existence of clear differences between layer IV and VPM neural state maps during the animal behavioral response and reward epochs also suggests that other afferents influence S1 granular layer dynamics.…”
Section: Discussionsupporting
confidence: 78%
“…Anatomical studies have shown that VPM sends multiple projections to the barrels in layer IV and to layer VI of S1 (Bernardo and Woolsey 1987;Killackey 1973;Lorente de No 1922;Woolsey and Van der Loos 1970), whereas POM projections to layer IV terminate mostly in the septa (Chmielowska et al 1989;Fabri and Burton 1991;Koralek et al 1988;Lu and Lin 1993). As the area occupied by barrels in layer IV is considerably larger than the area occupied by septa (Meyer et al 2013;Wimmer et al 2010;Woolsey and Van der Loos 1970), the observation that layer IV matches VPM neural state maps is in line with this anatomical data. However, the existence of clear differences between layer IV and VPM neural state maps during the animal behavioral response and reward epochs also suggests that other afferents influence S1 granular layer dynamics.…”
Section: Discussionsupporting
confidence: 78%
“…The fraction of cells that are neurons, as determined with NeuN alone, is uncertain because immunostaining is not all-ornone, there is no check by directly staining glia (we are not aware of a nuclear glial antibody), glia and neurons may not survive the disaggregation step equally, and the error magnitude in counting total cells (see above) is unknown. This issue is also relevant for stereology studies (38) that use NeuN for getting neuron and glia estimates.…”
Section: Evaluation Of Methods For Quantitative Studies Of Cell Numbementioning
confidence: 99%
“…The rodent primary somatosensory cortex is a very convenient model for studying the cortical processing of sensory information because of its well defined structural and functional layout that is invariant from animal to animal (Welker and Van der Loos, 1986;Meyer et al, 2013;Egger et al, 2012). In its layer IV, neurons are gathered into clusters called barrels that respect the same topology as the whiskers on the snout of the animal (Woosley and Loos, 1970).…”
Section: Q2mentioning
confidence: 99%